Post-Secondary Educational Leadership Working Remotely During a COVID-19 Pandemic in Saskatchewan, Canada: Exploring Best Practices, Experiences, and the New Normal Post-Pandemic - Papp, Theresa (Therri) A.; Cottrell, Michael (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
This mixed methods research design focuses on post-secondary institutions in Saskatchewan, Canada, its employees’ experiences of working remotely, and the impact of the global COVID-19 pandemic on school leadership. Presented are the perceived challenges as well as the benefits of the new workplace since the COVID-19 crisis. Administrative and instructional leadership had changed dramatically. Most identified their quality of work as better or the same because of having fewer distractions, interruptions, and less wasted time at the workplace. The participants’ interviews and survey responses describe the necessary adaptation, flexibility, mental health and wellness, accountability, workload intensification, and future expectations of the workplace and leadership once the pandemic is over.